2015
DOI: 10.1002/jcc.24013
|View full text |Cite
|
Sign up to set email alerts
|

Bis(azulene) “submarine” metal dimer sandwich compounds (C10H8)2M2 (M = Ti, V, Cr, Mn, Fe, Co, Ni): Parallel and opposed orientations

Abstract: The opposed and parallel structures for the binuclear bis(azulene) "submarine" sandwiches (C10H8)2M2 (M = Ti, V, Cr, Mn, Fe, Co, Ni) have been optimized using density functional theory. The lowest energy (C10H8)2 M2 structures of the early transition metals Ti, V, Cr, and Mn have the azulene units functioning as bis(pentahapto) ligands to each metal atom similar to the azulene ligand in the long-known molybdenum carbonyl complex (η(5),η(5)-C10H8 )Mo2 (CO)6 . The metal-metal bonds in these early transition meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…This remarkably simple reparameterization has generally minor effects on other thermodynamical parameters, based on the G2 test set, compared to the significant effect it had on spin-state splittings. While it is understood that B3LYP* is also not a universally accurate functional, it still has been demonstrated to be highly successful in many varied contexts, and is still routinely used[140][141][142][143][144][145].…”
mentioning
confidence: 99%
“…This remarkably simple reparameterization has generally minor effects on other thermodynamical parameters, based on the G2 test set, compared to the significant effect it had on spin-state splittings. While it is understood that B3LYP* is also not a universally accurate functional, it still has been demonstrated to be highly successful in many varied contexts, and is still routinely used[140][141][142][143][144][145].…”
mentioning
confidence: 99%
“…The metal centre can bond to both rings simultaneously, forming η 5 + 1 , η 5 + 2 and η 7 + 2 bonds. [15,[34][35][36][37] Korichi et al have reported the relative energy of the isomers of several mononuclear Az complexes. Their results do not show a clear trend on the preference of the metal for one of the two rings.…”
Section: Introductionmentioning
confidence: 99%